Regulation Networks Driving Vasculogenic Mimicry in Solid Tumors - Hernández de la Cruz, Olga N.; López-González, José Sullivan; García-Vázquez, Raúl; Salinas-Vera, Yarely M.; Muñiz-Lino, Marcos A.; Aguilar-Cazares, Dolores; López-Camarillo, César; Carlos-Reyes, Ángeles (Frontiers in Oncology, 2020)
Vasculogenic mimicry (VM) is a mechanism whereby cancer cells form microvascular structures similar to three-dimensional channels to provide nutrients and oxygen to tumors. Unlike angiogenesis, VM is characterized by the development of new patterned three-dimensional vascular-like structures independent of endothelial cells. This phenomenon has been observed in many types of highly aggressive solid tumors. The presence of VM has also been associated with increased resistance to chemotherapy, low survival, and poor prognosis. MicroRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are non-coding RNAs that regulate gene expression at the post-transcriptional level through different pathways. In recent years, these tiny RNAs have been shown to be expressed aberrantly in different human malignancies, thus contributing to the hallmarks of cancer. In this context, miRNAs and lncRNAs can be excellent biomarkers for diagnosis, prognosis, and the prediction of response to therapy. In this review, we discuss the role that the tumor microenvironment and the epithelial-mesenchymal transition have in VM. We include an overview of the mechanisms of VM with examples of diverse types of tumors. Finally, we describe the regulation networks of lncRNAs-miRNAs and their clinical impact with the VM. Knowing the key genes that regulate and promote the development of VM in tumors with invasive, aggressive, and therapy-resistant phenotypes will facilitate the discovery of novel biomarker therapeutics against cancer as well as tools in the diagnosis and prognosis of patients.